Armenian Alienated Society: from Diagnosis to Action - Harutyunyan, Manuk (Տիգրան Մեծ)
The article in concentrated form, presented our monographic work “the Modern Armenian society and the philosophy of alienated consciousness.” The study shows that the alienation is of systemic nature. The mood of alienation is inherent not only to the legislative, executive and judicial authorities but also political parties, public organizations, mass media, and electoral system. The article may be of interest to specialists in problems of alienation, undergraduates, graduate students and teachers of humanitarian higher educational establishments.
Keywords: Political Philosophy; Sociology